The RTSC: Leveraging the Migration from Event-Triggered to Time-Triggered Systems - Scheler, Fabian; Schröder-Preikschat, Wolfgang (Proceedings of the 13th IEEE International Symposium on Object/Component/Service-oriented Real-time Distributed Computing (ISORC '10), 2010)
In this paper we present a prototype of the RTSC - the Real-Time System Compiler. The RTSC is a compiler-based tool that leverages the migration from event-triggered to time-triggered real-time systems. For this purpose, it uses an abstraction called Atomic Basic Blocks (ABBs) which is used to capture all relevant dependencies of the event-triggered system in a so-called ABB-graph. This ABB-graph is transformed by the RTSC and finally mapped to a statically computed schedule that could be executed by standard time-triggered real-time operating systems. Moreover, we demonstrate the applicability of our approach and the operation of our prototype by transforming the event-triggered implementation of a real-world embedded system into a trime-triggered equivalent. © 2010 IEEE.
UnivIS-Import:2015-04-16:Pub.2010.tech.IMMD.IMMD4.therts
Keywords: ABBs; RTSC; Real-Time Systems; Event-Triggered Systems; Time-Triggered Systems